Coated Polyolefin
Patent Information
- Application Number
- JP2023561233
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-05
- Filing Date
- 2021-12-27
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2041-12-27
AI Technical Summary
Existing porous polymers face challenges in achieving high adsorption capacity while maintaining high liquid permeability, making it difficult to efficiently adsorb and elute analytes.
A coated substrate is developed with a polyolefin substrate having a functionalized polymer layer, featuring flow-through pore structures and specific pore sizes, formed by combining polyolefin substrates with porogens, monomers, and a polymerization initiator to create a thin functional polymer layer.
The coated substrate enables efficient adsorption and elution of analytes with high surface area and liquid permeability, allowing for applications in solid phase extraction and solvent elution, and supports various chemical functionalities.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] (Priority information) This application claims priority to U.S. Patent Application No. 63 / 170,950, entitled "COATED POLYOLEFINS," filed April 5, 2021, the contents of which are incorporated by reference in their entirety herein. [Background technology]
[0002] Porous polymers can be used as adsorbents in preparing samples for analytical separation and analysis. They can be used for analyte retention, concentration, or matrix exclusion. In some cases, the porous polymer is immersed in a liquid sample to adsorb the analytes, and then immersed in an elution solvent. Polymers can have high surface areas that can accommodate adsorption capacity, but historically, it has been difficult to formulate polymers that have relatively high adsorption capacity with high liquid permeability. Thus, there is a long-felt need in the art for such polymers. Summary of the Invention
[0003] To meet the stated long felt need, the present disclosure provides a coated substrate comprising a polyolefin substrate having a functionalized polymer layer disposed thereon, the polyolefin substrate having a flow-through pore structure with pore sizes ranging from about 5 microns to about 250 microns, the functionalized polymer layer having a thickness ranging from about 1 micron to about 20 microns, and the pore structure of the layer having pore sizes ranging from about 1 nm to about 100 nm.
[0004] The coated substrate may be formed by a process that provides a polyolefin substrate, in which one or more porogens, one or more monomers, and a polymerization initiator are combined with the polyolefin substrate, and the monomers are polymerized to form a functional polymer layer on the polyolefin substrate. [Brief description of the drawings]
[0005] In the drawings, which are not necessarily drawn to scale, the same numerals may represent similar components in different views. Similar numerals with different letter suffixes may represent different instances of similar components. The drawings illustrate generally, by way of example, but not by way of limitation, various aspects discussed in the present document. In the drawings: [Figure 1] Photographs of uncoated and coated polypropylene mesh exposed to Nile Blue A. [Diagram 2] 1 provides scanning electron micrographs of uncoated and coated polyethylene particles. [Diagram 3] 1 provides scanning electron micrographs comparing uncoated sintered polyethylene (PE) disks with coated sintered PE disks at different magnifications. [Figure 4] Photograph of Porex 4902 sintered polyethylene coated with porous DVB that was cut in half after being dipped in two different dyes. [Diagram 5] 1 is a graph of the percentage of analyte adsorbed from solution to the coated disks. [Figure 6] 1 is a scanning electron micrograph of a polymer layer on a sintered PE substrate. [Figure 7] 1 is a scanning electron micrograph of latex particles electrostatically attached to a sulfonated polymer layer of a coated disk. [Figure 8] 1 provides photographs of dye adsorption experiments of grafted and non-grafted DVB coated discs. [Figure 9] 1 is a scanning electron micrograph of a cross section of a coated substrate. [Figure 10] FIG. 1 is a chromatogram of a sample of anions analyzed by ion chromatography using Reagent Free Ion Chromatography (RFIC). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0006] The present disclosure may be understood more readily by reference to the following detailed description of the preferred embodiments and examples contained therein.
[0007] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. In case of conflict, the present document, including definitions, shall control. Preferred methods and materials are described below, although methods and materials similar or equivalent to those described herein can be used in practice or testing. All publications, patent applications, patents, and other references mentioned herein are incorporated by reference in their entirety. The materials, methods, and examples disclosed herein are illustrative only and are not intended to be limiting.
[0008] The singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.
[0009] As used in this specification and the claims, the term "comprising" includes the embodiments "consisting of" and "consisting essentially of." As used herein, the terms "comprise," "include," "having," "has," "can," "comprise," and variations thereof are intended to be open-ended transitional phrases, terms, or words that require the presence of the specified components / steps and permit the presence of other components / steps. However, such descriptions should be construed to describe compositions or processes as "consisting of" and "consisting essentially of" the listed components / steps, which permits the presence of only the specified components / steps with any resulting possible contaminants, and excludes other components / steps.
[0010] As used herein, the terms "about" and "at or about" mean that the quantity or value in question may be approximately or approximately the same as another value specified. As used herein, it is generally understood to be a nominal value indicating a variation of ±10%, unless otherwise indicated or inferred. The term is intended to convey that similar values promote the same results or effects as described in the claims. That is, it is understood that the amounts, sizes, formulations, parameters, and other quantities and characteristics need not be exact, but can be approximated and / or larger or smaller as necessary, reflecting tolerances, conversion factors, rounding, measurement errors, etc., and other factors known to those skilled in the art. In general, the amounts, sizes, formulations, parameters, or other quantities or characteristics are "about" or "approximate", whether or not they are expressly stated as such. When "about" is used before a quantitative value, it is understood that the parameter also includes the specific quantitative value itself, unless otherwise specified.
[0011] Unless otherwise indicated, numerical values should be understood to include numerical values that are the same when reduced to the same number of significant digits, and numerical values that differ from the stated value by less than the experimental error of conventional measuring techniques of the type described in this application to determine the value.
[0012] All ranges disclosed herein are inclusive of the recited endpoints, independent of the endpoints, 2 grams and 10 grams, and all intermediate values. The endpoints of the ranges and any values disclosed herein are not limited to the exact ranges or values, but are sufficiently imprecise to include values that are approximations of these ranges and / or values.
[0013] As used herein, approximation terms may be applied to modify any quantitative expression that may vary without resulting in a change in the basic function involved. Thus, values modified by terms such as "about" and "substantially" may not be limited to the precise values specified. In at least some instances, approximation terms may correspond to the precision of an instrument for measuring the value. The modifier "about" should also be considered to disclose a range defined by the absolute values of the two endpoints. For example, the expression "about 2 to about 4" also discloses the range "2 to 4". The term "about" may refer to plus or minus 10% of the indicated number. For example, "about 10%" may indicate a range of 9% to 11%, and "about 1" may mean 0.9 to 1.1. Other meanings of "about" may be apparent from the context, such as rounding, for example, "about 1" may also mean 0.5 to 1.4. Additionally, the term "comprising" should be understood to have the open-ended meaning of "including," but it also includes the closed meaning of the term "consisting." For example, a composition that includes components A and B can be a composition that includes A, B, and other components, but can also be a composition that consists only of A and B. All documents cited herein are incorporated by reference in their entirety for all purposes.
[0014] The coated substrate comprises a polyolefin substrate having a functional polymer layer disposed thereon. In some embodiments, the polyolefin substrate comprises polyethylene, polypropylene, polymethylpentene, polynorbornene, cyclic olefin copolymer, or a combination thereof. In some embodiments, the polyolefin substrate comprises polyethylene, polypropylene, or both. The polyolefin substrate has a flow-through pore structure with pore sizes ranging from 5 microns to 250 microns. The functional polymer layer has a layer pore structure with a thickness ranging from 1 micron to 20 microns and pore sizes ranging from about 1 nm to 100 nm. In some embodiments, the polyolefin substrate is different from the functional polymer layer.
[0015] Pores can be classified by their connectivity. Pores that are open to the outside are called open pores and are accessible for molecules to fit inside the open pores if their relative sizes are right. Open pores can have blockages or can be open ended. Blocked pores can be called blind pores. Open ended pores connect to other openings and therefore have communication through the material to other openings, either of which can be called flow-through pores. Layer pores are those that are present within the functional polymer layer and can be composed of open pores and flow-through pores.
[0016] The functional polymer layer is a layer disposed on a polyolefin substrate. The layer may be considered a coating. In some embodiments, the layer completely covers the polyolefin substrate. In some embodiments, the layer partially covers the polyolefin substrate.
[0017] In some embodiments, the coated substrate has a total pore volume ranging from about 5% to about 70%. Examples of total pore volume ranges include 0% to 5%, 5% to 10%, 10% to 15%, 15% to 20%, 20% to 25%, 25% to 30%, 30% to 35%, 35% to 40%, 45% to 50%, 50% to 55%, 55% to 60%, 60% to 65%, 65% to 70%, or ranges defined by a combination of two or more of the foregoing ranges. The total pore volume is the sum of the volume of the flow-through pores and the volume of the layer pores of the polyolefin substrate. The total pore volume is the percentage of the volume that is pores compared to the total volume of the coated substrate.
[0018] The coated substrate can be used as a device for performing solid phase extraction or to facilitate loading and / or elution of analytes with a solvent. For example, it can be coupled to a support. Other supports can be used, including, but not limited to, syringe barrel cartridges, chromatography columns, integrated sample preparation, injection and detection devices, membranes, microfluidic devices, pipette tips, multi-well plates, strips, plates, disks, hollow tubes, rods, etc. The support can be hydrophobic, hydrophilic, or can be made hydrophilic or hydrophilic. The coated substrate can be disposed on the surface of a supporting device or embedded within a channel or tube in the device.
[0019] In some embodiments, the polyolefin substrate is a porous material comprising polyethylene, polypropylene, polymethylpentene, polynorbornene, cyclic olefin copolymer, or a combination thereof. In some embodiments, the polyolefin substrate comprises polyethylene (PE). In some embodiments, the polyolefin substrate comprises polypropylene (PP). In some embodiments, the polyolefin substrate comprises both PE and PP. It has a flow-through pore structure with pore sizes ranging from 5 microns to 250 microns, such as 5 microns to 25 microns, 25 microns to 50 microns, 50 microns to 75 microns, 75 microns to 100 microns, 100 microns to 125 microns, 125 microns to 150 microns, 150 microns to 175 microns, 175 microns to 200 microns, 200 microns to 225 microns, 225 microns to 250 microns, or a range defined by a combination of two or more of the foregoing ranges. It should be noted that pore sizes may have irregular shapes, but pore sizes are expressed herein as an approximation of the equivalent pore diameter if the pore were spherical.
[0020] In some embodiments, the polyolefin substrate can be any porous solid structure that provides sufficient solvent and analyte access and porosity. Exemplary structures of polyolefin substrates include, but are not limited to, fibers, sheets, screens, disks, rods, tubes, woven meshes, pressed or molded shapes, and sintered articles. The fibers can be textiles woven into fabrics or made into nonwoven mats or thin paper-like sheets. In some embodiments, the polyolefin substrate comprises sintered particles. The sintered particles can be a porous mass formed by fusing particles together through heat or pressure without liquefying the particles. The polyolefin particles can be nonporous, irregularly shaped, or spherically shaped. However, fusing nonporous particles together creates a void volume that provides porosity to the resulting sintered particles. This void volume forms a liquid passageway through the porous mass and can be referred to as flow-through pores.
[0021] In some embodiments, the polyolefin substrate is not porous.
[0022] In some embodiments, the polyolefin substrate is about 0.1 mm thick prior to coating. 2 / g ~ approx. 1m 2 / g. An example of a surface area is 0.1 m 2 / g~approx.0.2m 2 / g, 0.2m 2 / g~approx.0.3m 2 / g, 0.3m 2 / g~approx.0.4m 2 / g, 0.4m 2 / g~approx.0.5m 2 / g, 0.5m 2 / g~approx.0.6m 2 / g, 0.6m 2 / g ~ approx. 0.7m 2 / g, 0.7m 2 / g~approx.0.8m 2 / g, 0.8m 2 / g~approx. 0.9m 2 / g, 0.9m 2 / g ~ approx. 1m2 / g, or a range defined by a combination of two or more of the foregoing ranges.
[0023] The functional polymer is coated onto the substrate as a thin layer. The weight ratio of the functional polymer layer to the polyolefin substrate ranges from 1 / 100 to about 50 / 100. For example, the weight ratio can be expressed as the weight of the monomer of the functional polymer incorporated into the polyolefin substrate divided by the weight of the polyolefin substrate (e.g., ratio = monomer weight for functional polymer / weight of polyolefin substrate). The functional polymer is formed by polymerization of the monomer to form a layer on the polyolefin substrate. In some embodiments, the ratio of the monomer to the substrate is 1 / 100 to 50 / 100 by weight prior to polymerization. Examples of ratios are ranges of 1 / 100 to 50 / 100, 10 / 100 to 50 / 100, 20 / 100 to 50 / 100, 30 / 100 to 50 / 100, 40 / 100 to 50 / 100, 1 / 100 to 40 / 100, 1 / 100 to 30 / 100, 1 / 100 to 20 / 100, 1 / 100 to 10 / 100, or ranges defined by a combination of two or more of the foregoing.
[0024] In some embodiments, the functional polymer layer is not covalently bonded to the polyolefin. It is believed that the use of a porogenic solvent partially dissolves the polyolefin substrate, allowing for physical intermixing of the polyolefin structure with the functional polymer as the polyolefin substrate is formed.
[0025] The thickness of the functional polymer layer is in the range of 1 micron to 20 microns, such as 1 micron to 5 microns, 5 microns to 10 microns, 10 microns to 15 microns, 15 microns to 20 microns, or a range defined by a combination of two or more of the foregoing ranges. In some embodiments, the layer is homogenous. The functional polymer layer is homogenous when the dye is distributed throughout the coated substrate as in Example 3. The thickness of the functional polymer layer can be seen in a cross-sectional SEM as shown in FIG. 9.
[0026] The functional polymer has a pore structure of the layer having pore sizes in the range of about 1 nm to 100 nm, such as 1 nm to 10 nm, 10 nm to 20 nm, 20 nm to 30 nm, 30 nm to 40 nm, 40 nm to 50 nm, 50 nm to 60 nm, 60 nm to 70 nm, 70 nm to 80 nm, 80 nm to 90 nm, 90 nm to 100 nm, or a range defined by a combination of two or more of the aforementioned ranges. The pore structure of the layer refers to the pores within the functional polymer. The functional polymer is configured to bind chemicals and / or ions from a liquid solution. It is believed that the pore structure of the layer is formed, in part, by the use of a porogenic solvent during the formation of the functional polymer layer.
[0027] The functional polymer contains a large number of pores and therefore has a large surface area. In some embodiments, the surface area is about 25 m 2 / g~about 800m 2 / g, e.g., 300m 2 / g~about 800m 2 / g, e.g., 300m 2 / g~about 400m 2 / g, approx. 400m 2 / g~about 500m 2 / g, approx. 500m 2 / g~about 600m 2 / g, approx. 600m 2 / g~about 700m 2 / g, approx. 700m 2 / g~about 800m 2 / g, or a range defined by a combination of two or more of the foregoing ranges.
[0028] The functional polymer may have hydrophobic, hydrophilic, medium hydrophobic / hydrophilic, ion exchange and affinity moieties. These moieties provide different functions for the functional polymer layer. In some embodiments, the layer is present on the surface of a polyolefin substrate and is a homogenous layer of polyolefin.
[0029] In some embodiments, the coated substrate further comprises one or more additional (or second, third, ...) functional polymer layers on top of the functional polymer layer. The second functional polymer layer may be hydrophobic, hydrophilic, or may have ion-exchange functionality. It may partially cover the functional polymer layer below it, or it may completely cover the functional polymer layer below it. Depending on the additional functional polymer layer, subsequent chemistry may be applied. For example, a second functional polymer layer of styrene / DVB and n-heptane would be non-polar (hydrophobic). This functional polymer layer may be sulfonated to create a polar (hydrophilic / water-wettable) cation-exchange phase. A functional polymer layer of vinylbenzylchloride (VBC) / divinylbenzene (DVB) and n-heptane may be aminated to create an anion-exchange phase. The DVB functional polymer layer may be grafted with various vinyl monomers to create polar and / or ion-exchange phases. In another embodiment, when the functional polymer layer contains negatively charged sulfonic acid groups, positively charged anion exchange particles (e.g., latex particles) can be ionically bonded to the negatively charged sulfonate groups.
[0030] The functional polymer is formed from a solution of monomers on a polyolefin substrate. The monomers can be hydrophobic and / or hydrophilic monomers and include at least one crosslinking moiety. Examples of aromatic (styrenic) monomers include styrene, DVB, VBC, ethylvinylbenzene (EVB), and derivatives thereof. Hydrophilic monomers include acrylates, methacrylates, and derivatives thereof. In some embodiments, the functional polymer comprises a polymer formed from monomers selected from styrene, DVB, VBC, EVB, acrylates, methacrylates, derivatives thereof, and combinations thereof. In some embodiments, the functional polymer comprises a copolymer formed from the monomers DVB and EVB. Note that in one embodiment, technical grade DVB may contain 80% DVB (both meta and para isomers) with about 20% EVB as an impurity. In some embodiments, the functional polymer is crosslinked. Crosslinking monomers include any monomer having two or more groups capable of forming a covalent bond with a monomer, oligomer, or polymer chain. In the case of VBC copolymers, the VBC groups of the copolymer can be reacted with amines to form attached amine groups to provide an anion exchange phase.
[0031] Porogenic Solvent The polymer formed on the polyolefin substrate is porous and is produced using a porogenic solvent. The porogenic solvent dissolves in the monomer mixture to partially solubilize or swell the polyolefin substrate. It is not a solvent for the resulting polymer. The Hildebrand solubility parameter (delta, δ) can be used as a rough guide to predict the interaction of the porogen with the substrate. In general, the closer the δ values of the porogen and the substrate, the more likely the porogen will solvate or swell the polyolefin substrate. Exemplary Hildebrand solubility parameters for PE and PP are 16-17 MPa. 0.5In some embodiments, partial solubility means that the difference between the δ of the porogen and the δ of the polyolefin substrate is 4 or less, such as 3 or less, 2 or less, or 1 or less. Suitable porogenic solvents include, but are not limited to, aliphatic, such as hexane, heptane, octane, and decane; alicyclic, such as cyclopropane, methylcyclohexane, and heptalene; aromatic hydrocarbons, such as toluene, xylene, ethylbenzene, diethylbenzene; halogenated aromatics; and halogenated aliphatic, such as dichloromethane, dichloroethane, and trichloroethane. In some embodiments, the porogen is an aliphatic, such as hexane, heptane, octane, decane, and combinations thereof. The porogenic solvents can be used in combination of two or more of them individually or in combination. In some embodiments, the ratio of porogen to monomer is 1 / 10 to 400 / 10 by weight, such as 1 / 10 to 10 / 10, 10 / 10 to 50 / 10, 50 / 10 to 100 / 10, 100 / 10 to 150 / 10, 150 / 10 to 200 / 10, 200 / 10 to 250 / 10, 250 / 10 to 300 / 10, 300 / 10 to 350 / 10, 350 / 10 to 400 / 10, or a range defined by a combination of two or more of the aforementioned ranges. As an example, the ratio of porogen to monomer can be expressed by the formula Ratio = Mass of porogen / Mass of monomer. In some embodiments, the one or more porogens include n-heptane and the one or more monomers include divinylbenzene, and the ratio of porogen to monomer is in the range of 1 / 1 to 20 / 1.
[0032] In some embodiments, for non-polar monomers (such as aryl monomers like styrene, vinyl benzyl chloride, divinylbenzene), example porogens include hexane, heptane, octane, cyclohexanol, decanol, dodecanol, benzene, toluene, tetrahydrofuran, and halogenated porogens like chlorobenzene, trichloroethylene, trichloromethane. In some embodiments, for polar monomers (such as acrylates), example porogens include methanol, butanol, methyl isobutyl ketone, dimethylformamide, and dimethylsulfone. In some cases, mixtures of porogens can be used to affect the surface area and pore size of the functionalized porous polymer layer.
[0033] Method for coating a substrate The coated substrate is formed by a process that provides a polyolefin substrate. A porogen, one or more monomers, and a polymerization initiator are combined with the polyolefin substrate. The monomers are polymerized to form a functional polymer layer on the polyolefin substrate. The mixture of monomers and polyolefin substrate is agitated during at least a portion of the polymerization.
[0034] Examples of the polymerization initiator include radical polymerization initiators such as benzoyl peroxide, dicumyl peroxide, 4,4-azobis(4-cyanovaleric acid), diisopropyloxycarbonate, t-butylperoxy-2-ethylhexanoate, t-butylperoxypivalate, t-butylperoxydiisobutyrate, lauroyl peroxide, dimethyl 2,2'-azobisisobutyrate (MAIB), azobisisobutyronitrile (AIBN), and azobiscyclohexanecarbonitrile (CAN).
[0035] In one embodiment, the polyolefin substrate is combined with a monomer solution containing one or more monomers, one or more porogens, and a polymerization initiator. In some embodiments, the porogen also acts as a swelling agent for the polyolefin substrate. The sealed container containing the polyethylene particles and the monomer solution is placed in an agitation device and heated until polymerization is complete. Examples of agitation include, but are not limited to, rotating, shaking, and tumbling.
[0036] After polymerization, the coated substrate can be chemically cleaned to remove any unreacted monomer, porogen, and reaction by-products. Cleaning can include the use of organic solvents, acids, bases, and / or salt solutions along with agitation, stirring, sonication, and / or heating.
[0037] In some embodiments, secondary chemical steps are performed on the polymer coated polyolefin. These include adding additional functional groups to impart, but are not limited to, specific hydrophobic, hydrophilic, and ion exchange functionalities. Multiple chemical steps can be performed to impart the desired functionality.
[0038] Based on the "inertness" of polyolefins, the ability to coat porous and impermeable polyolefin substrates with hydrophobic and hydrophilic porous polymers was unexpected. The fact that the polymer uniformly coats the porous substrate without filling or clogging the through-holes of the impermeable substrate was also a surprising result, as the coated substrate allows liquids to flow at flow rates of up to 20 mL / min under low pressures such as 2 atmospheres or vacuum, while still being in the form of a thin disk and capable of adsorbing chemicals. Ion exchange coated substrates have capacities ranging from 0.1 to 3 milliequivalents / gram of coated substrate. Non-polar (reverse phase) coated substrates can have loading capacities ranging from 0.05 to 1 milliequivalents / gram of coated substrate. As an example, a hydrophobic material that can be loaded onto a non-polar coated substrate can be xylene. Thus, the coated substrate can be configured to be mounted onto a laboratory pipette tip to change or alter the chemical composition of the output solution at relatively low pressure. This change in chemical composition can occur by binding ions, analytes, and / or matrix chemicals from the input liquid sample. In some cases, the input liquid sample can be acidic or basic and can thus be partially or completely neutralized through ion exchange with hydronium or hydroxide ions, such that the output liquid from the coated substrate has an altered or neutral pH. In one embodiment, the coating occludes about 5%-75% of the void volume. The ability to coat these inert polyolefin substrates with polymers that allow for subsequent chemical reactions opens the possibility of a very wide range of functional polymers being applied for specific applications.
[0039] Working Example Example 1. Extruded polypropylene mesh with a functional polymer layer Discs 7.9 mm in diameter were die cut from Industrial Netting Discs XN5340, a 0.031 inch thick extruded polypropylene mesh with 0.033 inch by 0.045 inch holes. The nominal open area is approximately 30%.
[0040] The screen (1.0 g) was added to a 20 ml scintillation vial. Then, 1.0 g of a monomer solution containing 3.0 parts n-heptane and 1.0 parts of an 80 wt % divinylbenzene (DVB) solution with 0.25% AIBN was added (equal mass of monomer solution to screen). The vial was heated to 65° C. and stirred for 72 hours. The vial was removed and the disk was rinsed with 10 mL of clean acetone (2 times) and dried. The mass gain of the screen was about 6%, indicating a successful coating process.
[0041] Discs of untreated and treated screens were placed in 4 mL of 30 ppm Nile Blue A with 1% IPA (for wetting). Figure 1 is a photograph of the screens after 48 hours. The disc on the left is the untreated (raw) screen and the disc on the right is the coated / treated screen, showing that the Nile Blue was adsorbed onto the coated polypropylene.
[0042] Example 2. Polyethylene particles with a functional polymer layer Mipelon PM-200 from Mitsui Chemicals consists of 10 micron high molecular weight polyethylene particles. To a 20 ml vial was added 1.00 g Mipelon, 5.00 g 20 parts n-heptane, and 1 part divinylbenzene (80% purity) with 1% AIBN (by mass of divinylbenzene) as a thermal free radical initiator. The vial was heated to 65° C. and stirred for 52 hours. After polymerization, the particles were allowed to settle and the excess liquid (n-heptane) was decanted. The particles were then rinsed with three aliquots of acetone (15 mL per aliquot) to remove excess monomer or porogen. The supernatant was cloudy after the first two rinses, indicating some particles and colloidal DVB. After the final rinse, the vial was placed in an oven for 1 hour with the cap removed to dry.
[0043] Scanning electron micrographs in Figure 2 show uncoated and coated polyethylene particles. A thin layer of DVB polymer, as well as colloidal-sized particles of polymer, can be seen across the surface of the PE particle. The DVB polymer layer can be derivatized to add additional chemical functionality, including hydrophilic and / or ion-exchange groups.
[0044] Example 3. Sintered Polyethylene Substrate with a Functional Polymer Layer In a 25 ml bottle, a 0.31 inch diameter disk of Porex 4902 sintered polyethylene (0.25 inch thick, pore size 15-45 microns) was combined with an equal mass of monomer solution containing 2.0 parts n-heptane and 1.0 part DVB (80% purity) with 1% AIBN (by mass of divinylbenzene). The vial was heated to 65°C and stirred for 44 hours. The vial was removed and the disk was rinsed with 15 mL of acetone (2 times) and dried. The mass gain of the coated disk was approximately 33%, indicating near complete incorporation of the polymer onto the sintered polyethylene disk. The 33% mass gain resulted from the fact that the monomer solution was 33% DVB (1 part DVB / 2 parts n-heptane + 1 part DVB) and the sintered polyethylene was of equal mass to the monomer solution. Scanning electron micrographs comparing uncoated and coated sintered polyethylene disks are shown in Figure 3.
[0045] To test the ability of the coated 4902 disks to absorb dyes, the disks were moistened with isopropyl alcohol and then placed in two dye solutions (100 ppm Quinaldine Red and 100 ppm Nile Blue A dye). The disks were soaked for 30 minutes, removed, and rinsed with deionized water to remove the dye in the open pores of the sintered polyethylene. The disks were cut lengthwise, and Figure 4 shows a photograph of the results. The polymer layer significantly increased the surface area of the sintered PE, allowing for efficient dye adsorption.
[0046] Example 4. Dye adsorption onto sintered rods with functional polymer layers Molded sintered polyethylene rods of approximately 5 mm diameter and 21 mm length were coated with a monomer solution containing 2.0 parts n-heptane and 1.0 part DVB (80% purity) with 1% AIBN (by weight of divinylbenzene). Three different porous rods, A, B and C, were coated with the monomer solution and tested for adsorption efficiency using 3 mL of 10 ppm Nile Blue A. Adsorption efficiency was measured by determining the difference in visible absorbance between the original dye solution and the dye solution after contacting the coated rod (probe) and stirring for 60 minutes. The results are shown in the table below.
[0047] [Table 1]
[0048] Example 5. Adsorption of alkylphenones onto sintered polyethylene with a DVB-functional polymer layer Disks (0.21 inch diameter x 0.12 inch thick) were punched out of Porex 4901 sintered polyethylene sheet. The disks were then coated with a monomer solution containing 2.0 parts n-heptane and 1.0 part DVB (80% purity) with 0.1% AIBN (by weight of divinylbenzene). After polymerization, the disks were washed with acetone and dried. Each coated disk contained approximately 10 mg of DVB layer. Five of each of the coated disks were inserted onto a 0.026 inch diameter, 3.5 inch long stainless steel rod. A solution containing 10 ppm of four alkylphenones (acetophenone, eugenol, propiophenone, and butyrophenone) was analyzed by high performance liquid chromatography (HPLC) with UV detection at 230 nm. The coated disks on the rods were inserted into 1 mL of alkylphenone solution and then placed in an ultrasonic bath for 5 minutes. The disks were then removed and the solution was analyzed by HPLC. This process was repeated at 10, 20, 30 and 40 minutes. The percentage of each analyte adsorbed from the solution onto the disk is shown in Figure 5. Each bar in the cluster of bars in Figure 5 is arranged and represented in order moving from left to right as acetophenone, eugenol, propiophenone, and butyrophenone, respectively.
[0049] Example 6. Sintered PE with styrene / divinylbenzene and latex functional polymer layers A solution consisting of 96% styrene, 4% DVB (80% purity), and 1% AIBN (by combined weight of styrene and DVB) was diluted with 2 parts by weight of n-heptane (w / w). An equal weight of the monomer / n-heptane solution was then added to a 0.2 inch diameter Porex 4901 sintered polyethylene disk, sealed in a glass bottle, and placed in a 65° C. oven for 46 hours. After the disk was coated with the resulting styrene / DVB polymer, the disk was rinsed in acetone and then dried. Figure 6 shows the polymer layer on the sintered PE substrate.
[0050] The coated substrate was then combined with concentrated sulfuric acid (10 parts by weight of sulfuric acid to 1 part by weight of polymer coated substrate, w / w) and placed in a 95° C. oven for 1 hour. Upon removal from the oven, the disk was light brown in color, indicating that the styrene / DVB polymer had been sulfonated. The sulfonated disk was now negatively charged and water wettable. A portion of the sulfonated disk in hydronium form was used later as described in Example 9. The sulfonated disk was then neutralized in sodium hydroxide and rinsed with deionized water. A solution of colloidal anion-exchange latex particle polymer with a diameter of about 400 nm was then added to the sulfonated disk. Examples of latex particles can be found in U.S. Pat. Nos. 5,532,279, 10,118,171, and 4,101,460, which are incorporated by reference in their entireties. Because these anion-exchange latex particles are positively charged, the latex particles electrostatically adhered to the negatively charged sulfonated polymer layer of the disk, as shown in FIG.
[0051] This anion-exchange latex flocculated coated sintered polyethylene can be used to extract anions and cations from solution.
[0052] Example 7. Aminoacrylate grafting onto sintered polyethylene with a DVB-functional polymer layer Porex 4901 (0.21 inch diameter x 0.125 inch thick) disks were coated with 2.0 n-heptane:1.0 DVB (80% purity) containing 1% AIBN (of divinylbenzene) as described in Example 3. An equal mass of monomer solution was added to the Porex disks and allowed to react at 65°C for 48 hours. After washing with acetone and drying, the coating efficiency was determined to be 99% and each disk contained approximately 9.2 mg of porous DVB.
[0053] For grafting, a solution of 2-[(methacryloyloxy)ethyl]trimethylammonium chloride (MAO) was prepared by adding 1.3 g of 75% MAO to 98.7 g of deionized water. To the diluted MAO monomer solution was added 0.13 g of a free radical thermal initiator, 4,4'-azobis(4-cyanopentanoic acid) (ABCPA). The grafting procedure consisted of adding 10 4901 DVB coated disks each (total of 92 mg DVB) to three separate vials, then adding MAO monomer at a mass of 10, 20, and 30% of the mass of the DVB layer, respectively.
[0054] Three vials with 10 DVB coated disks in each vial were prepared and labeled 2A (10%), 2B (20%) and 2C (30%). The disks were wetted with acetone (approximately 0.25 mL for 10 disks) and the excess acetone was allowed to evaporate so that only a small amount of liquid acetone was present. The monomer and initiator solutions were then added. The three vials were placed in a 60° C. oven and allowed to polymerize for 7 days.
[0055] After polymerization, water was added to the disk. The disk was wetted by water, indicating that the grafting reaction had made the disk hydrophilic. The disk was rinsed and sonicated to remove any residual monomer or initiator.
[0056] Dye adsorption experiments were performed without stirring. One each of the 10, 20, and 30% grafted MAO disks was placed in a 4 mL vial and 2.0 mL of 100 ppm acid fuchsin in 5 mM HCl was added. For reference, a non-grafted DVB coated disk was wetted with acetone and added to 1.5 ml of acid fuchsin (vial 5). After 24 hours, the disk was removed and rinsed with water. Figure 8 shows that the grafted disks adsorbed significantly more dye than the non-grafted disks (vial 5). Since grafting creates anion exchange functionality and the dye is anionic, the grafted disks are expected to retain more dye than the non-grafted disks.
[0057] Example 8. SEM of coated substrate. Twenty-nine sintered polyethylene disks (Porex 4901) with a total mass of 1.00 g and dimensions of 0.21 inch diameter and 0.22 inch height were combined with 1.00 g of a monomer solution of 0.666 g n-heptane, 0.330 g of industrial grade divinylbenzene (80% purity) and 0.0033 g of the thermal radical initiator azobisisobutyronitrile (AIBN). The disks and monomer solution were placed in a 65°C oven, stirred, and allowed to polymerize for 24 hours. The porous DVB polymer coated disks were removed from the oven and rinsed with three aliquots of 20 mL acetone, then dried in a 65°C oven for 1 hour. A single disk was cut in half with a single edge razor and then prepared for imaging by sputtering with gold using a Thermo Fisher Scientific Phenom World ProX scanning electron microscope. A representative image is shown in Figure 9. This image shows a cross-section of a porous polymer coating with a rough surface surrounding a sintered polyethylene substrate. The thickness of the porous polymer layer ranges from approximately 2 microns to 10 microns.
[0058] Example 9. Flow-through extraction. A 1.00 mL pipette tip was fitted with a sulfonated cation exchange (hydronium form) coated substrate as described in Example 6, but without colloidal latex anion exchange particles. The coated substrate was used in flow-through mode to neutralize basic samples prior to anion analysis by ion chromatography. Figure 10 shows the ion chromatogram obtained after passing 1.00 mL of sample 1, containing anions in 0.1 M sodium hydroxide, through a pipette tip containing a cation exchange coated substrate to neutralize the sodium hydroxide and then injecting into the ion exchange system. Neutralizing the sodium hydroxide results in well-separated peaks with high chromatographic efficiency. Sample 2 has the same composition as sample 1, but sample 2 was analyzed without neutralization using a flow-through pipette tip containing a cation exchange coated substrate. The bottom chromatogram in Figure 10, analyzing untreated sample 2, showed poorer peak resolution for peaks 1-5.
Claims
1. A coated substrate comprising: a polyolefin substrate having a functional polymer layer disposed thereon; the polyolefin substrate has a flow-through pore structure with pore sizes ranging from 5 microns to 250 microns; and the functional polymer layer has a thickness in the range of 1 micron to 20 microns and the pore structure of the layer has a pore size in the range of 1 nm to 100 nm; The coated substrate, wherein the functional polymer layer is not covalently bonded to the polyolefin substrate, and the functional polymer layer has a surface area of from 25 m 2 / g to 800 m 2 / g.
2. The coated substrate of claim 1, wherein the weight ratio of said functional polymer layer to said polyolefin substrate ranges from 1 / 100 to 50 / 100.
3. The coated substrate of claim 1, wherein the coated substrate has a pore volume of from 5% to 70%.
4. 10. The coated substrate of claim 1, wherein the polyolefin substrate comprises polyethylene, polypropylene, polymethylpentene, polynorbornene, a cyclic olefin copolymer, or a combination thereof.
5. 10. The coated substrate of claim 1, wherein the functional polymer layer comprises a polymer formed from styrene, divinylbenzene, vinylbenzyl chloride, acrylates, methacrylates, ethylvinylbenzene, derivatives thereof, or combinations thereof.
6. The coated substrate of claim 1 , wherein the polyolefin substrate comprises a form selected from fibers, sheets, screens, woven meshes, and sintered particles.
7. 10. The coated substrate of claim 1, further comprising one or more additional functional polymer layers over the functional polymer layer, the one or more additional functional polymer layers being hydrophobic, hydrophilic, or having ion exchange functionality.
8. 10. The coated substrate of claim 1, wherein the functional polymer layer comprises negatively charged sulfonate groups and positively charged anion exchange particles are ionically bonded to the negatively charged sulfonate groups.
9. 10. The coated substrate of claim 1, wherein the functional polymer layer comprises positively charged amino groups and negatively charged cation exchange particles are ionically bonded to the positively charged amino groups.
10. providing the polyolefin substrate; combining one or more porogens, one or more monomers, and a polymerization initiator with the polyolefin substrate to form a mixture; initiating polymerization of the monomer to form the functional polymer layer; and agitating the mixture during at least a portion of the polymerization; 2. A process for forming the coated substrate of claim 1 comprising:
11. 11. The process of claim 10, wherein the porogen comprises a solvent selected from aliphatic, cycloaliphatic, aromatic hydrocarbons, halogenated aliphatic, and halogenated aromatic.
12. 11. The process of claim 10, wherein the one or more porogens comprise n-heptane and the one or more monomers comprise divinylbenzene, and the weight ratio of the porogen to monomers ranges from 1 / 1 to 20 / 1.
13. The process of claim 10 , wherein the functional polymer layer is formed in a sealed container while the mixture is being agitated.
14. The process of claim 10, wherein the weight ratio of the porogen to monomer is from 1 / 10 to 400 / 10 by mass and / or the ratio of the monomer to substrate is from 1 / 100 to 50 / 100 by mass.
15. 11. The process of claim 10, wherein the Hildebrand solubility parameters of the porogen and the monomer differ by no more than 4.